Pilot project «development of medical rehabilitation system in russian federation». Protocol of second stage - G. E. Ivanova; E. V. Melnikova; A. A. Shmonin; D. M. Aronov; A. A. Belkin; A. F. Belyaev; R. A. Bodrova; M. G. Bubnova; T. V. Builova; I. E. Mishina; S. V. Prokopenko; A. M. Sarana; et al. (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The Pilot project «Development of medical rehabilitation system in Russian Federation» is the large Russian project which is intended to transform system of rehabilitation care for patients with stroke, heart attack, and after total hip arthroplasty. The present article is the second one in the series of publications of the Project’s protocol. The publication shows the criteria of translation from 1 to 2 stages of rehabilitation and from 2 to 3 stages for all three profiles of the project. Working peculiarities of the second phase of the project are prescribed which realizes the new model of rehabilitation with assessment according to the ICF, determination of rehabilitation diagnosis, work in multidistsiplinary team and the introduction of a new speciality – ergotherapy.